PEMBUATAN DAN UJI MUTU FISIK MASKER PEEL-OFF DARI PATI JAGUNG (Zea Mays L.) - Dzulasfi Dzulasfi (Akademi Farmasi Yamasi Makassar, 2022)
Has carried out research on the Manufacturing and Physical Quality Test of Peel-Off Masks from Corn Starch (Zea Mays L.). This study aims to determine whether corn starch (Zea Mays L.) can be made in the form of a Peel-Off mask and meets the physical quality test. Results of Organoleptic Observations, pH Tests, Spreadability Tests and Dry Time Tests, 2.5% and 7.5% formulations met the skin pH requirements, namely 6.50 and 6.82. Based on the results of the research that has been carried out, it can be concluded that masks from corn starch can be formulated in the form of peel-off gel masks that meet the physical quality test standards.